Forms of Interaction Between Supply Chain Strategy and Business Structures in the Far Eastern Federal District - V. Varkulevich, Tatyana; R. Pashuk, Natalya (International Journal of Supply Chain Management, 2020)
For Supply Chain executives the first step is to clearly understand how the enterprise chooses to compete. This is important not only for the obvious reason of working together in the same direction, but also because Supply Chain has to enable the Business Strategy; it is not merely an operational department. According to the data of survey conducted by the All-Russian Center for the Study of Public Opinion, more than half of the employers of the Far Eastern Federal District are faced with the problems of staffing, which is explained by the inconsistency of the requirements of enterprises with the quality of supply chain strategy. The organization of cooperation between business structures and supply chain strategy of the region ensures an increase in the quality of performance, stimulates a decline in unemployment and population shift from the Far East, which affects the socio-economic development of the federal district. In addition, the university-enterprise partnership helps to reduce the time for the development and implementation of research products, the commercialization of knowledge, the development of entrepreneurship, and, as a result, an increment in GRP and the innovative potential of the region. Therefore, the main objective of this article is to analyze the main forms of collaboration between supply chain strategy and business in the Far Eastern Federal District to determine the regions of the Far Eastern Federal District and supply chain strategy, which are characterized by a high degree of involvement of the business sector of economic activity into the activities of management. The main sources of information were informational and analytical materials for monitoring the performance of institutes in 2018. To provide thematic justification of the research, an analysis of the regulatory framework for the purpose of identifying the role of business structures in solving the socio-economic problems of territories has been carried out.